2005
DOI: 10.1007/s11240-004-7013-y
|View full text |Cite
|
Sign up to set email alerts
|

Auxin pulses and a synergistic interaction between polyamines and ethylene inhibitors improve adventitious regeneration from apricot leaves and Agrobacterium-mediated transformation of leaf tissues

Abstract: The effect, on adventitious regeneration from apricot leaf explants and transformation of leaf tissues, of auxins pulses with NAA and 2, 4-D D was tested. Addition of the polyamines putrescine and spermidine to the regeneration medium, alone or in combination with the ethylene inhibitors silver thiosulphate and aminoethoxyvinylglycine, were also tested to design a procedure that improved transformation efficiency. Spermidine at 2 mM in combination with 0.5 lM aminoethoxyvinylglycine and four-day pulses with tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…AgNO 3 is an ethylene action inhibitor and ethylene inhibits S-adenosyl methionine decarboxylase, which in turn promotes polyamine levels, which are implicated during flowering (Bais et al 2000). The ethylene biosynthesis inhibition by AgNO 3 is well documented in other plant systems (Pua et al 1996;Vinod Kumar et al 2009): it has been reported that addition of AgNO 3 to the culture media greatly improves regeneration of many dicot and monocot cultures as in case of Vanilla planifolia (Giridhar et al 2001), apricot (Petri et al 2005), Coffea canephora (Sridevi et al 2010), and Malaxis acuminata (Meena et al 2010). The interrelation between AgNO 3 , ethylene, SAM and polyamines has been well reviewed by Bais et al (2000).…”
Section: Resultsmentioning
confidence: 96%
“…AgNO 3 is an ethylene action inhibitor and ethylene inhibits S-adenosyl methionine decarboxylase, which in turn promotes polyamine levels, which are implicated during flowering (Bais et al 2000). The ethylene biosynthesis inhibition by AgNO 3 is well documented in other plant systems (Pua et al 1996;Vinod Kumar et al 2009): it has been reported that addition of AgNO 3 to the culture media greatly improves regeneration of many dicot and monocot cultures as in case of Vanilla planifolia (Giridhar et al 2001), apricot (Petri et al 2005), Coffea canephora (Sridevi et al 2010), and Malaxis acuminata (Meena et al 2010). The interrelation between AgNO 3 , ethylene, SAM and polyamines has been well reviewed by Bais et al (2000).…”
Section: Resultsmentioning
confidence: 96%
“…Ethylene has been reported to negatively affect the transformation efficiency of plants by A. tumefaciens (Ezura et al 2000;Chakrabarty et al 2002;Burgos and Alburquerque 2003;Petri et al 2005;Han et al 2005;Seong et al 2005), so that if acdS is introduced into A. tumefaciens, the resulting strain's ability to lower the ethylene level in the target, together with its increased persistence, may improve the transformation efficiency for some recalcitrant plant species. Experiments to test this hypothesis are currently in progress in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of aminoglycoside antibiotics for selection of apricot nptII -transformed leaf tissues was studied (Burgos and Alburquerque 2003 ;Petri et al 2005a ) and the transformation procedure optimized by adding 2,4-D during the cocultivation period (Petri et al 2005b ) . However, transformed plants were not obtained.…”
Section: Transgenicsmentioning
confidence: 99%